2022
DOI: 10.1056/evidoa2200137
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic versus Normothermic Temperature Control after Cardiac Arrest

Abstract: BACKGROUND The evidence for temperature control for comatose survivors of cardiac arrest is inconclusive. Controversy exists as to whether the effects of hypothermia differ per the circumstances of the cardiac arrest or patient characteristics.METHODS An individual patient data meta-analysis of the Targeted Temperature Management at 33 C versus 36 C after Cardiac Arrest (TTM) and Hypothermia versus Normothermia after Out-of-Hospital Cardiac Arrest (TTM2) trials was conducted. The intervention was hypothermia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…1 The two randomised TTM trials ('TTM trial' and 'TTM2 trial') studied hypothermia at 33 versus 36 C, and 33 C versus normothermia with early treatment of fever in out-of-hospital cardiac arrest (OHCA). 2,3 Both trials found similar survival and neurological outcomes in the respective temperature groups, also when pooled in a meta-analysis defining normothermia as 36.0-37.7 C. 4 In contrast, the HYPERION trial, including both OHCA and in-hospital cardiac arrest found a better neurological outcome in patients treated with 33 as compared to 37 C. 5 The updated European Resuscitation Council and European Society of Intensive Care Medicine (ESICM) guidelines recommend to actively prevent fever (core temperature >37.7 C) targeting 37.5 C but state that evidence for targets between 32 and 36 C are insufficient for recommendation for or against. 6 However, given the equipoise between hypothermia and normothermia in OHCA and the wide range of target temperatures having been recommended before the last guideline update, current practice may vary.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…1 The two randomised TTM trials ('TTM trial' and 'TTM2 trial') studied hypothermia at 33 versus 36 C, and 33 C versus normothermia with early treatment of fever in out-of-hospital cardiac arrest (OHCA). 2,3 Both trials found similar survival and neurological outcomes in the respective temperature groups, also when pooled in a meta-analysis defining normothermia as 36.0-37.7 C. 4 In contrast, the HYPERION trial, including both OHCA and in-hospital cardiac arrest found a better neurological outcome in patients treated with 33 as compared to 37 C. 5 The updated European Resuscitation Council and European Society of Intensive Care Medicine (ESICM) guidelines recommend to actively prevent fever (core temperature >37.7 C) targeting 37.5 C but state that evidence for targets between 32 and 36 C are insufficient for recommendation for or against. 6 However, given the equipoise between hypothermia and normothermia in OHCA and the wide range of target temperatures having been recommended before the last guideline update, current practice may vary.…”
Section: Introductionmentioning
confidence: 88%
“…Normothermia was defined as 36.0-37.7 C in line with a recent meta-analysis. 4 Data on number of admitted patients in 2022 were collected from the open data portal of the Swedish Intensive Care Registry. 10 A structured telephone survey was conducted in all (= 53) Swedish Levels 2 and 3 ICUs during April and May 2022.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 50 One recent meta-analysis comparing hypothermic to normothermic management did not find a difference in 6-month mortality or functional outcomes using the Rankin score for both older and younger age groups. 69 While older age is associated with decreased survival after cardiac arrest, there is limited evidence on functional and neurologic outcomes specific to geriatric patients. This lack of data may impact code status discussions with patients and their family members and should be a goal of future studies.…”
Section: System-specific Considerations In Older Adultsmentioning
confidence: 99%